What impact did the COVID-19 pandemic have on hospital complaints? A 7-year retrospective study in a Swiss public hospital - Angela Greco; Riccardo Bocci; Hans Stricker; Stefano Lucchina (BMC Health Services Research)
Abstract Background Patient dissatisfaction frequently results in formal complaints, which can reveal critical issues related to care quality, communication, and organizational performance. The COVID-19 pandemic heightened public stress and may have contributed to an increase in complaints and staff burnout. Despite the importance of complaint analysis, long-term studies in this area - particularly in Switzerland - remain limited. This study examines how the pandemic influenced the volume and nature of formal complaints in a Swiss public hospital over a seven-year period. Methods We conducted a retrospective observational study with an exploratory design in a Swiss public hospital with longstanding experience in complaint management. A single hospital was selected as a case study due to its leadership continuity, stable management structure, and mature quality assurance system. Semi-annually complaint incidence from 2017 to 2023 was analyzed using control charts and linear regression to identify temporal trends. The impact of the pandemic was assessed by comparing the pre-COVID (2017–2019) and post-COVID (2021–2023) periods. A statistically significant increase in complaints in the post-COVID period (p < 0.05, two-proportion Z-test) prompted further analysis by complaint category (clinical, managerial, relational). Finally, we assessed whether this rise could be linked to clinical quality by comparing the proportion of complaints that did not report actual but only potential clinical harm to patient health (classified by the hospital’s quality service as near-miss events) with those involving health-related concerns. The study used fully anonymized data, with no narrative or personal information and involved no patient interaction. Finally, we assessed whether this rise in complaints could be linked to clinical quality by comparing the proportion of cases referring to incidents with actual harm (classified as adverse) with those involving only potential harm (classified by the hospital’s quality service as near-miss events). The study used fully anonymized data, containing no narrative or personal information, and involved no patient interaction. Results A total of almost 800 complaints were recorded across 527,851 hospital admissions (1.5 per 1,000). Complaint incidence increased significantly over time (R² = 0.59, p = 0.0013), with peaks in S2 2022 and S1 2023. A statistically significant post-pandemic rise in complaint rates was observed (p < 0.05), particularly in relational complaints (+ 68%), followed by managerial (+ 59%) and clinical (+ 44%). While the overall number of complaints rose, the proportion of near-miss events was higher post-COVID, and no cases of severe harm were reported within the complaints received after 2020. This suggests a shift in the nature of dissatisfaction raised, with fewer complaints indicating actual patient harm. Conclusions This study provides evidence of a marked increase in patient complaints - especially those related to relational aspects - after the COVID-19 pandemic. These findings highlight the need for targeted hospital strategies to improve communication, strengthen patient-provider relationships, and support staff. Investments in training and the systematic complaint monitoring can help identify early signs of dissatisfaction and guide quality improvement. Further research is needed to assess the long-term effects of these trends and the impact of relational care interventions on patient experience.